Virulence factors and beta-lactamase production among vancomycin-resistant Enterococcus faecalis isolated from clinical samples and hospital environment - David, Moses; Imonitie, Kennedy; Osuntoyinbo, Richard; Olawale, Adetunji (International Journal of Biological Research, 2016)
Enterococcus faecalis, though opportunistic pathogen has emerged as one of the leading nosocomial pathogens and has been implicated in different human infections. The severity of the infections caused by this organism is largely due to its complex pathogenic process. The objective of this study was to determine the carriage of virulence factors and vanA gene among the strains of vancomycin-resistant E. faecalis isolated from hospitals. Standard methods were used for isolation, antibiotic susceptibility and detection of virulence factors in the isolates. A total of one hundred and twenty three (123) samples were screened out of which 69 (45.70 %) yielded E. faecalis. The highest percentage of the isolates was recovered from the environment followed by the clinical samples. Children surgical ward had the highest occurrence of the test organism followed by male surgical ward. All the isolates were resistant to both amoxycillin/clavulanic acid and ceftazidime, while 98.55%, 89.86% and 53.62% were resistant to ampicillin, cefuroxime and gentamicin respectively. Only twenty seven (39.13%) of the isolates were resistant to the vancomycin. Among the vancomycin-resistant isolates, haemolysin had the highest occurrence (60.29%) followed by caseinase (55.88%). A total of 16 (59.26%) were beta-lactamase positive while 8 (29.63%) out of the isolates (vancomycin-resistant) were non-biofilm former while vanA genes was detected in 9 (33.33%) of the isolates. This study gives an insight to antibiotic resistant pattern of circulating Enterococcus faecalis and also the isolate showed varying patterns of virulent factors.